Theoretical Calculation for Pure Epoxy and Lead by Monte Carlo - Dhameer A.Mutlak, Ali Abdul Kadhim Ruhaima, Israa Taha Ibrahim, Ibrahim Mourad Mohammed (Pakistan Journal of Medical & Health Sciences, 2023)
Theoretical calculation for pure epoxy and lead by Monte Carlo code in MATLAB 14 was used in this research, Structure of these simulation can be very useful to gain a useful knowledge of different process and how these relate for each other’s. The primary and the physical process which associated with gamma ray’s transmission. Most interactions through matter is scattering, photoelectric effects, and pair production. Effects of a gamma ray passing and interacts with a medium are the results of multiple independent interactions. With heavier elements, a lower photovoltaic cross-section resulted in wide path length for photons. The light elements, such as epoxy, the dominant spectrum of energy transmitted for epoxy is 0.7 MeV. For epoxy, gamma rays deposited energy with the photoelectric absorption and the Compton scattering, but for driving, the dominant precipitated energies are by pair formation. The primary interactions are predominant with the epoxy medium is either by photoelectric or by Compton reaction and the probabilities interactions depending upon cross-sections. Keyword: epoxy composites, gamma irradiation, Monte Carlo